Determinación del comportamiento de 15 cultivares de musa spp y 2 heliconias frente a la inoculación de ralstonia solanacearum, agente causal del moko bacteriano. - Veloz Martínez, Karla Berenisse (2015)
This research was conducted at the field level and at the State Laboratory Technical University of Quevedo, located at Km 1 Vía Quevedo to Santo Domingo. The main objective was to establish the behavior of fifteen cultivars of Musa spp and two cultivars of Heliconia spp against challenge insulation Moko (Ralstonia solanacearum) and specifically determine the type of R. solanacearum presented in the littoral zone (biovar) and define levels of resistance / tolerance of the cultivars Musa spp against Moko (Ralstonia solanacearum). This disease first detected in 1840 in British Guiana and appeared in epidemic form in Trinidad in 1895, today present in several banana producing countries of America, where it causes major annual losses. This study was placed in a completely randomized design (CRD), 17 treatments (cultivars of Musa and Heliconia) in three repetitions, each experimental unit was composed of 4 seedlings. The response of the cultivars to inoculation of R. solanacearum determined levels of resistance / susceptibility to be considered in the management of the disease. The span of just one month it took to kill the bacteria in all plants Michel Gross, H. Wagner Barraganete and determined the level of susceptibility of the cultivars evaluated. These three were considered highly susceptible cultivars. Under this criterion, on the opposite side of the scale we have grade H. latispata as resistant. With the Filipino cultivate a distinction (Moderately susceptible) considering that no plant died in the trial period is done. The other cultivars showed different degrees of tolerance. Then the group made up of the two cultivars maqueños, the two Dominicans group bananas; Vinces, Orito, Cavendish and Williams whose reaction to the disease reached present level of chlorosis in the second and third sheet so they fall into the category of moderately tolerant or resistant.